The Hidden Epidemic: The Prevalence and Impact of Concurrent Liver Diseases in Patients Undergoing Liver Transplantation in Australia and New Zealand - Jess Howell, MBBS(Hons), PhD, MSc(Epi), PGradDip(PH); Avik Majumdar, MBBS(Hons), MPHTM, PhD; Michael Fink, MBBS; Mandy Byrne, PhD; Geoff McCaughan, MBBS, PhD; Simone I. Strasser, MBBS, PhD; Michael Crawford, MBBS, MD; Peter Hodgkinson, MBBS; Katherine A. Stuart, MBBS, PhD; Caroline Tallis, MBBS(Hons); John Chen, MBBS; Alan Wigg, MBBS, PhD; et al. (Transplantation Direct, 2022)
Background. Prevalence of concurrent liver diseases among liver transplant recipients and impact on posttransplant outcomes are unknown. Methods. This retrospective study included adult liver transplants between January 1‚ 1985‚ and December 31‚ 2019‚ from the Australian and New Zealand Liver and Intestinal Transplant Registry. Up to 4 liver disease causes were recorded for each transplant; concurrent liver diseases were defined as >1 liver disease indication for transplantation, excluding hepatocellular carcinoma. Impact on posttransplant survival was determined using Cox regression. Results. A total of 840 (15%) of 5101 adult liver transplant recipients had concurrent liver diseases. Recipients with concurrent liver diseases were more likely male (78% versus 64%) and older (mean age 52 versus 50 y). A higher proportion of liver transplants for hepatitis B (12% versus 6%), hepatitis C (33% versus 20%), alcohol liver disease (23% versus 13%), and metabolic-associated fatty liver disease (11% versus 8%, all P < 0.001) were identified when all indications were included than with primary diagnosis only. The number and proportion of liver transplants performed for concurrent liver diseases have increased from 8 (6%) during Era 1 (1985–1989) to 302 (20%) during Era 7 (2015–2019; P < 0.001). Concurrent liver diseases were not associated with increased posttransplant mortality (adjusted hazard ratio, 0.98, 95% confidence interval, 0.84-1.14). Conclusions. Concurrent liver diseases are increasing among adult liver transplant recipients in Australia and New Zealand; however, they do not appear to impact posttransplant survival. Reporting all liver disease causes in the transplant registry reports provides more accurate estimates of liver disease burden.